Synthesis and Aggregation of In2O3 Nanoparticles: Impact of Process Parameters on Stoichiometry Changes and Optical Properties - Siedl, Nicolas; Gügel, Philipp; Diwald, Oliver (Langmuir, 2013)
Metalorganic chemical vapor synthesis provides agglomerated In2O3 nanoparticles with a low abundance of particleparticle interfaces. Via exposure to bulk water and subsequent dehydration treatment these powders can be transformed into networks of aggregated nanoparticles. Two major effects arise from the associated emergence of particleparticle interfaces: an enhanced susceptibility to annealing induced n-type doping and a significant red-shift of the optical absorption threshold by 0.2 eV. On the basis of control experiments with pure water, we further explored the impact of the environmental gas atmosphere during annealing on the integral ensemble properties. We found that residual water vapor promotes the mutual attraction of particles, facilitates their condensation, and generates particleparticle interfaces. This work may prove to be of great value for the reproducible production and formulation of percolating metal oxide nanoparticle networks with high control over particle aggregation state, on the one hand, and n-type conductivity as well as optical properties, on the other.